2003
DOI: 10.1002/hup.496
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of depression: are there any?

Abstract: Simple tests for antidepressant-like activity, such as 5-HTP-induced syndrome or reserpine-induced hypomotility, are often mechanism-based tests, pharmacologically specific for certain known classes of therapeutically successful antidepressant agents. Many of these behavioural assays have been superseded by neurochemical techniques such as in vivo microdialysis. In contrast to these mechanistic-based models, investigators have also endeavoured to reproduce in the laboratory, factors that are believed to precip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(68 citation statements)
references
References 129 publications
1
63
0
4
Order By: Relevance
“…However, there have been numerous models investigated, but many of them do not possess all three of the above noted characteristics, and, as such, will not be discussed in this review. O'Neil and Moore 11 wrote: "the OBX test is valuable in that it has been one of the few tests that mimics the slow onset of antidepressant action reported in clinical studies" and concluded that "the convergence of data from markers as diverse as behaviour, neurochemistry, as well as endocrine and immune function, suggest that this model will continue to shed valuable light on depressive mechanisms and treatment for some time to come".…”
Section: Skelin Et Al Neurochemical and Behavioural Changes In Rmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there have been numerous models investigated, but many of them do not possess all three of the above noted characteristics, and, as such, will not be discussed in this review. O'Neil and Moore 11 wrote: "the OBX test is valuable in that it has been one of the few tests that mimics the slow onset of antidepressant action reported in clinical studies" and concluded that "the convergence of data from markers as diverse as behaviour, neurochemistry, as well as endocrine and immune function, suggest that this model will continue to shed valuable light on depressive mechanisms and treatment for some time to come".…”
Section: Skelin Et Al Neurochemical and Behavioural Changes In Rmentioning
confidence: 99%
“…7,[10][11][12][13] Neuronal changes have been reported in structures deemed to play an important role in affective and cognitive functioning, which are also the target of the olfactory bulb projections, such as the amygdala, greater hippocampal formation, and the bed nucleus of the stria terminalis. 10,14 The amygdala and hippocampus have important influences on frontal cortical striatal circuitry.…”
Section: Skelin Et Al Neurochemical and Behavioural Changes In Rmentioning
confidence: 99%
“…Evidence for antidepressant efficacy of 5-hydroxytryptophan 3.1. Preclinical evidence for efficacy of 5-hydroxytryptophan 5-HTP is commonly given to rats or mice to test the SSRI potency of putative antidepressants (O'Neil & Moore, 2003). This simple in vivo test measures the potency of a compound in potentiating the serotonin syndrome induced by the administration of 5-HTP (Grahame- Smith, 1971).…”
Section: Factors Affecting 5-hydroxytryptophan Availability For Serotmentioning
confidence: 99%
“…Sıçanın açık kolu görecek şekilde labirent üzerine yerleştirilmesinin nedeni, sıçanların doğuştan açık ve yüksek yerlerden korkuyor olmalarıdır [4,24]. Anksiyeteye işaret eden davranış değerlendirmeleri; kapalı kol üzerinde geçen zamanın uzaması, donakalma süresindeki artış, açık kola giriş sayısındaki azalma, merkezi alanda gezinme süresindeki azalma ve iki ayağı üzerinde kalkıp havayı koklama sayısındaki ve süresindeki artışlardır [25].…”
Section: Yükseltilmiş Labirent Testleriunclassified
“…Sıçanlar için koku alma temel duyu modalitesi olduğundan, olfakter bulbuslarının bilateral olarak alınması ile depresyon yaratılmaktadır [25,34]. Bu modelin kullanıldığı antidepresan aktivite değerlendirme çalışmalarında, sıçanların açık alandaki davranışlarında hiperaktivite azalması kaydedilmiştir [35].…”
Section: Olfaktor Bulbektomi Testiunclassified